Heparin-Binding Haemagglutinin, a New Tool for the Detection of Latent Mycobacterium tuberculosis Infection in Hemodialysis Patients - Dessein, Rodrigue (Public Library of Science, 2013)
BACKGROUND: Patients with end-stage renal disease (ESRD) and latently infected with Mycobacterium tuberculosis (LTBI) are at higher risk to develop tuberculosis (TB) than healthy subjects. Interferon-gamma release assays (IGRAs) were reported to be more sensitive than tuberculin skin tests for the detection of infected individuals in dialysis patients. METHODS: On 143 dialysis patients prospectively enrolled, we compared the results from the QuantiFERON®-TB Gold assay (QFT), to those of an IGRA in response to in vitro stimulation of circulating mononuclear cells with the mycobacterial latency antigen Heparin-Binding Haemagglutinin purified from Mycobacterium bovis BCG (native HBHA, nHBHA). RESULTS: Seven patients had a past history of active TB and 1 had an undetermined result with both IGRAs. Among the other 135 patients, 94 had concordant results with the QFT and nHBHA-IGRA, 40.0% being negative and therefore not latently infected, and 29.6% being positive and thus LTBI. Discrepant results between these tests were found for 36 patients positive only with the nHBHA-IGRA and 5 only with the QFT. CONCLUSIONS: The nHBHA-IGRA is more sensitive than the QFT for the detection of LTBI dialysis patients, and follow-up of the patients will allow us to define the clinical significance of discrepant results between the nHBHA-IGRA and the QFT.